The Effect of Using Augmented Reality-Based Media on Increasing the Attention of Students with Intellectual Disabilities - Hanif, Ellora Fauziyyah; Junaidi, Ahsan Romadlon; Novianti, Ranti; Dewantoro, Dimas Arif (Jurnal ORTOPEDAGOGIA, 2025)
One of the most common problems experienced by students with intellectual disabilities is attention problems. Attention problems in children with intellectual disabilities can worsen the impact of academic disabilities on children. To improve attention skills, effective learning strategies and attractive media are needed. The learning program using android-based augmented reality using tablet devices serves as a stimulator tool that not only creates interest but also student and teacher engagement in the learning process. The participants in this study are 10-year-old children with mild intellectual disabilities who attend SLB Idayu 1 Malang City. This research aims to analyze and evaluate the use of augmented reality-based media on attention in learning for children with intellectual disabilities. Data collection is done by observation with indicators of student on-task time. This research uses Single Subject Research experimental method with A-B-A design and descriptive statistical technique to analyze the data. The results showed a temporary increase in student attention to the learning program with augmented reality. This is due to several factors involved in learning activities. Factors that contribute to the results of this study include unfavorable environment, distraction, teaching style and the influence of the child's condition, while internal factors include boredom or illness and decreased motivation and interest.